MODUL BERSUPLEMEN UTAMA SEBAGAI GENERALISASI DARI MODUL BERSUPLEMEN - ., Fitriani (MATEMATIKA, 2015)
An R-module M is called supplemented if every submodule of M has a supplement in M. Principally supplemented modules are defined as generalizations of lifting, principally lifting and supplemented modules. In this paper, we will characterize principally supplemented modules as a generalization of supplemented module respect to duo module and distributive module.